Government Spending Effect on HDI Indragiri Hilir: An ECM Approach - Fajar Fadly; Yurnal Edward (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Indragiri Hilir Regency has the second lowest Human Development Index compared to the newly established regencies and cities in Riau province. However, Indragiri Hilir Regency has a relatively high allocation of development budget and per capita income compared to other regencies and cities. The objectives of the study were to determine whether the effect of the Indragiri Hilir government expenditure realization on the Human Development Index is cointegrated, to examine the long-term impact of expenditure realization on education, health, infrastructure, environmental, and social protection functions on the Human Development Index in Indragiri Hilir, and to analyze the short-term effects of environmental and social protection functions on the Human Development Index. The study employed the Error Correction Model (ECM) method, utilizing data from the period 2007 to 2021 obtained from the Directorate General of Fiscal Balance (DJPK) of the Indonesian Ministry of Finance for independent variables, while dependent variables were sourced from the Central Statistics Agency (BPS). The study findings revealed that government spending has a cointegrated influence on the Development Index. Furthermore, it was observed that the realization of government spending on education, health, and infrastructure functions did not significantly affect the Human Development Index in the Indragiri Hilir regency. In contrast, the realization of government spending on environmental functions showed a significant positive correlation. Similarly, the realization of Indragiri Hilir's government spending on social protection functions had a significant negative correlation. Therefore, the government of Indragiri Hilir Regency should assess expenditure realization on education, health, and infrastructure functions and introduce innovative programs. Increased spending on social protection led to a reduction in the Human Development Index.